Synchronous papillary thyroid carcinoma and cervical lymph node metastasis of breast cancer: a case report - Xiaoxiao, An; Yuanfan, Qian; Jianyong, Zhang; Yuan, Chen (Frontiers in Oncology, 2026)
Breast and thyroid cancers can occasionally manifest concurrently; however, the underlying molecular mechanisms remain poorly understood. In cases of high-risk breast cancer, there is a propensity for metastasis to the cervical lymph nodes. When such a scenario coincides with thyroid cancer, there is a risk of misdiagnosing the cervical lymph node metastasis as being related to the thyroid cancer, thereby complicating clinical diagnosis. This report examines a case involving synchronous papillary thyroid carcinoma and cervical lymph node metastasis originating from breast cancer. The patient, a 50-year-old Asian female, presented with bilateral neck masses and a medical history of thyroid nodules and triple-negative breast cancer (TNBC). Ultrasonography identified abnormal lymph nodes on both sides of the neck, as well as a thyroid nodule. It was initially uncertain whether the lymphadenopathy was attributable to thyroid malignancy, recurrence and metastasis of breast cancer, or a combination of both. Fine-needle aspiration of the thyroid nodule confirmed the presence of papillary thyroid carcinoma (PTC), while biopsy and immunohistochemical analysis of the bilateral cervical lymph nodes revealed metastatic breast carcinoma. Positron emission tomography/computed tomography (PET/CT) imaging revealed the presence of multiple hypermetabolic lymph nodes in the bilateral supraclavicular fossae, mediastinum (stations 1, 2R/L, and 6R), and bilateral internal mammary regions, indicative of metastatic disease. Based on the clinical history and pathological findings, a diagnosis of synchronous metastasis from breast cancer and papillary thyroid carcinoma (PTC) was established. Following a multidisciplinary team discussion, the patient was promptly commenced on salvage chemotherapy and immunotherapy specifically targeting breast cancer. The concurrent occurrence of thyroid carcinoma and cervical metastases from breast cancer presents a significant diagnostic challenge for clinicians. Early pathological confirmation, in conjunction with clinical history, is crucial for devising appropriate treatment strategies and enhancing patient survival outcomes. The potential comorbidity between thyroid and breast cancer remains uncertain and warrants further investigation through both clinical and laboratory research.